Perlindungan Hukum Terhadap Saksi Pelapor Dalam Pemberantasan Tindah Pidana Pencucian Uang di Indonesia - Hanafiah, Yuliana; Sari, Nia Ayu Mayang (PT Elaborium Elevasi Indonesia, 2025)
Money laundering is a crime that affects all countries, including Indonesia. Money laundering is a very serious criminal act, often carried out openly by the perpetrators, involving both the perpetrators and the beneficiaries. The methods wed by these perpetrators for laundering money have become more widespread and almost uridetectable. For this reason, the government requires the public to cooperate as partners in combating and preventing money laundering crimes in Indonesia, acting as reporters who have knowledge of money laundering indicators arid the initial crimes related to it. Therefore, this study aims to examine how legal protection is arranged for whistleblower wimesses in the eradication of money laundering crimes in Indonesia, as well as how the implementation of Law No. 8 of 2010 regarding whistleblower witnesses in money laundering crimes is carried out in Indonesia. The research method used in this study is normative juridical research with a legal approach. The results of the study explain that legal protection for whistleblower witnesses in the eradication ofmoney laundering crimes in Indonesia plays a crucial role in handling the elimination of these crimes. This is in line with the legal protection of whistleblowers, which is regulated by law, ensuring the safety of the whistleblowars, wimesses, and their families, as well as the need for legal counseling provided by the government until the case is resolved. In handling the eradication of money laundering crimes in Indonesia, the government's efforts to provide legal protection to whistleblower witnesses include granting legal certainty and benefits in the fight against money laundering crimes in Indonesia.